2014 IEEE 40th Photovoltaic Specialist Conference (PVSC) 2014
DOI: 10.1109/pvsc.2014.6924983
|View full text |Cite
|
Sign up to set email alerts
|

Reactive ion etched black silicon texturing: A comparative study

Abstract: We report on significant progress towards the application of reactive ion etched (RIE) black silicon (b-Si) as an alternative to the most commonly applied front-side textures utilized in the crystalline silicon photovoltaics industry -random pyramids and isotexture. The as-etched b-Si surface displays approximately 1% front side reflectance weighted across the solar spectrum, outperforming both random pyramids (2.83%) and isotexture (6.06%) with optimized anti-reflection coatings. The b-Si front surface reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…8 Due to this field-effect, very low surface recombination rates have been reported for lowly doped b-Si, even lower than what could expected on the basis of the large b-Si surface area. [6][7][8]13 As result, interdigitated back contact solar cells with a conversion efficiency of 22.1% have recently been demonstrated with the lowly p-type doped b-Si front surface being passivated by ALD Al 2 O 3 . 2 Even though Al 2 O 3 provides excellent passivation of lowly doped b-Si, standard industrially produced solar cell architectures, such as the aluminum back surface field (Al-BSF) cell and passivated emitter and rear cell (PERC), fundamentally rely on a heavily n-type doped Si front surface.…”
mentioning
confidence: 99%
“…8 Due to this field-effect, very low surface recombination rates have been reported for lowly doped b-Si, even lower than what could expected on the basis of the large b-Si surface area. [6][7][8]13 As result, interdigitated back contact solar cells with a conversion efficiency of 22.1% have recently been demonstrated with the lowly p-type doped b-Si front surface being passivated by ALD Al 2 O 3 . 2 Even though Al 2 O 3 provides excellent passivation of lowly doped b-Si, standard industrially produced solar cell architectures, such as the aluminum back surface field (Al-BSF) cell and passivated emitter and rear cell (PERC), fundamentally rely on a heavily n-type doped Si front surface.…”
mentioning
confidence: 99%
“…Extracting S textured from the stabilized lifetime data results in values close to S planar (10.6 cm s −1 ) only for t RIE of 1.5 and 2 min (12.9 and 13.6 cm s −1 , respectively). We note that texturing with ICP for 3 min or shorter times in our equipment results in S textured values (before degradation) on par with or even better than the state‐of‐the‐art for p‐type CZ (11 cm s −1 in the review by Otto et al, 20 cm s −1 in the record b‐Si cells by Savin et al and 10 cm s −1 reported by Allen et al). This indicates potential for further efficiency improvements of b‐Si solar cells made by RIE texturing, if CCP is omitted from the texturing process.…”
mentioning
confidence: 46%
“…Compared to the typical front surface reflectance of ∼ 2 and ∼ 8 %, from conventionally textured mono- [8] 5 and multi-crystalline [9] Si solar cells, respectively, nanoscale texturing such as described in [10,11,12] offers a potential of improved power conversion efficiency for Si solar cells due to reduced reflectance loss.…”
Section: Introductionmentioning
confidence: 99%